2016
DOI: 10.3382/ps/pev447
|View full text |Cite
|
Sign up to set email alerts
|

Temperature during the last week of incubation. I. Effects on hatching pattern and broiler chicken embryonic organ development

Abstract: We investigated the effects of an eggshell temperature (EST) of 35.6, 36.7, 37.8, and 38.9°C applied from d of incubation (E) 15, E17, and E19 on hatching pattern and embryonic organ development. A total of 2,850 first-grade eggs of a 43-week-old Ross 308 broiler breeder flock were incubated at an EST of 37.8°C until E15. From E15, E17, or E19 onward, eggs were incubated at an EST of 35.6, 36.7, 37.8, or 38.9°C. Moment of internal pipping (IP), external pipping (EP), and hatch was determined, and organ develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…To balance oxygen requirement and oxygen availability in week 3 of incubation, it can be suggested that after E14, a lower EST than 37.8°C might be more optimal. Maatjens et al., 2016a , Maatjens et al., 2016b demonstrated that an EST of 36.7°C or even 35.6°C from E15 onward resulted in a higher YFBM and higher relative heart, intestine, liver, and bursa of Fabricius weights of neonatal chicks than an EST of 37.8°C throughout incubation.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…To balance oxygen requirement and oxygen availability in week 3 of incubation, it can be suggested that after E14, a lower EST than 37.8°C might be more optimal. Maatjens et al., 2016a , Maatjens et al., 2016b demonstrated that an EST of 36.7°C or even 35.6°C from E15 onward resulted in a higher YFBM and higher relative heart, intestine, liver, and bursa of Fabricius weights of neonatal chicks than an EST of 37.8°C throughout incubation.…”
Section: Introductionmentioning
confidence: 96%
“…When temperature is raised during incubation, embryo metabolism increases as broiler embryos act mainly as poikilotherms ( French, 1997 ), suggesting that embryonic development will be stimulated with a higher EST than 37.8°C. For the second week of incubation, this might be true, but in the third week of incubation, a higher EST than 37.8°C has been shown to negatively affect neonatal chick quality and posthatch performance ( Romanoff, 1936 ; Lourens et al., 2005 ; Hulet et al., 2007 ; Leksrisompong et al., 2007 ; Ipek et al., 2014 ; Maatjens et al., 2014b , 2016a ). Hatchlings incubated at an EST higher than 37.8°C during late incubation showed a poorer quality, expressed by a shorter length, more residual yolk ( RY ), worse navel score, and lower weights of various organs relative to their YFBM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At an activity concentration of 13.5 kBq/mL, the recovery coefficients for 18 (21). Considering that the organs of ostrich embryos are naturally larger than those of chicken embryos (e.g., liver size: 15 vs. 2 cm 3 ) (18,22), it is conceivable that imaging is comparable. This aspect has to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…E.g. Lourens et al [141], Molenaar et al [142], and Maatjens et al [143,144] demonstrated strong effects of incubation temperature on chicken quality at hatching.…”
mentioning
confidence: 99%